Varieties of service economies in Europe - Gisela Di Meglio; Andreas Pyka; Luis Rubalcaba (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
This paper identifies the varieties and dynamics of service economies in Europe, analysing the role of knowledge base and innovative efforts and their evolution across time and countries. Results based on aggregated macroeconomic data indicate that there is no convergence trend towards a single service economy model. Moreover, different service economies models can be associated with institutional and welfare state diversity. When analysing a comprehensive set of indicators at a disaggregated level a more detailed pattern of service economies emerges. The structural composition of countries plays a prominent role, while heterogeneity is driven by uneven knowledge bases and innovative efforts.
urn:nbn:de:bsz:100-opus-7031
Keywords: L80; O31; C38; 330; services; social models; innovation; knowledge; Europe; Dienstleistung; Dienstleistungsgesellschaft; Wissen; Innovation; Clusteranalyse; Aggregation; Wirtschaftsindikator; EU-Staaten